The existential impact of high-conflict divorce on children. (2nd January 2020) - Shumaker, David; Kelsey, Charlotte
ABSTRACT: While it has become clear that high-conflict divorce/separation can have both short- and long-term negative effects upon children, traditional measures of health and adjustment are limited in their ability to fully capture the depth and scope of this trauma. The impact of parental conflict and divorce can arguably be more deeply grasped by clinicians attuned to existential considerations. The authors argue in select cases certain theoretical underpinnings of Existential-Integrative Psychotherapy (EI) may reflect the lived experience of a young client. By extension, aspects of EI may benefit certain youth being treated from a Person-Centered Therapy (PCT) framework. The theoretical implications and potential applications of an integrated approach are explored.